Empowering Senior Cochlear Implant Users at Home via a Tablet Computer Application - Philips, Birgit (Am J Audiol, 2018)
PURPOSE: The introduction of connectivity technologies in hearing implants allows new ways to support cochlear implant (CI) users remotely. Some functionalities and services that are traditionally only available in an in-clinic care model can now also be accessed at home. This study explores the feasibility of a prototype of a tablet computer application (MyHearingApp [MHA]) in a group of senior experienced CI users at home, evaluating usability and user motivation. METHOD: Based on user feedback, a tablet computer application (MHA) for the Cochlear Nucleus 6 CP910 sound processor was designed implementing six different functionalities: (a) My Hearing Tests, (b) My Environment, (c) My Hearing Journey, (d) Tip of the Day, (e) Recipient Portal, and (f) Program Use and Events. The clinical evaluation design was a prospective study of the MHA in 16 senior experienced CI users. During 4 weeks, participants could freely explore the functionalities. At the end, the usability and their motivation for uptake and adherence were measured using a baseline and follow-up questionnaire. RESULTS: Based on the System Usability Score (as part of the follow-up questionnaire), a good level of usability was indicated (M = 75.6, range: 62.5–92.5, SD = 8.6). The ability to perform hearing tests at home is ranked as the most relevant functionality within the MHA. According to the Intrinsic Motivation Inventory (Deci, Eghrari, Patrick, & Leone, 1994) questionnaire (as part of the follow-up questionnaire), participants reported high levels of interest and enjoyment, found themselves competent, and did not experience pressure while working with the app. CONCLUSIONS: This study evaluated a tablet computer application (MHA) for experienced senior CI users by means of a prospective design, which provided novel insights into delivering CI care into the home of the CI user. The user feedback from this small-scale study suggests that the participants are open to take more responsibility for and to become a more active actor in their own hearing care, if only this is facilitated with the right tools. This may foster the evolution from a clinic-led to a more patient-centered care model, where CI users feel more empowered in the self-management of their hearing implant device.